Optimalisasi Pemanfaatan Ruang pada Hutan Rakyat untuk Mendukung Pengembangan Agrowisata Puncak Suroloyo, Kabupaten Kulon Progo, D.I. Yogyakarta - Singgih Utomo; Silvi Nur Oktalina; Wiyono Wiyono; Rochmad Hidayat; Puji Lestari; Ridla Arifriana; Dania Sintia (Pengabdian dan Pengembangan Masyarakat Sekolah Vokasi UGM, 2021)
The tourist visits to Suroloyo has increased due to the improvement of accessibility, supporting facilities, and information technology. However, the community forest surrounding Suroloyo is less optimum to support the tourism sector. Coffee as a new icon of Suroloyo could not fulfill the market demand yet, because the forest land resources are less managed. Hence, this community service activity aimed to: (1) identify the structure and composition of the community forest; (2) increasing the understanding of farmers on the optimization of land resource management; and (3) increasing the skill of farmers on coffee cultivation. The number of 35 members of the coffee farmer group in Keceme Village owned 0,35 ha of land on average. Albizia (Falcataria mollucana), saman (Meisopsis eminii) and mahogany (Swietenia macrophylla) dominate the forest stand, by the mean canopy cover of 53% (optimum cover for coffee is 40-60%). The on-farm training for the farmers and interactive discussion with an invited expert on coffee cultivation was held. In addition, the superior coffee seed from the Indonesian Coffee and Cocoa Research Institute are shared to the farmers with expectations of increasing productivity. The motivation and ability of the farmers on coffee cultivation in order to support the agritourism in Suroloyo were increased.